ANALISIS PENGGUNAAN VIDEO PEMBELAJARAN IPA PADA PEMBELAJARAN TATAP MUKA TERBATAS DI SD MUHAMMADIYAH 9 SURABAYA - Aris Wahyuningsih; Meirza Nanda Faradita; Fajar Setiawan (Universitas PGRI Adi Buana Surabaya, 2022)
This study aims to describe the use of science learning videos in limited face-to-face learning at SD Muhammadiyah 9 Surabaya. The research method used in this research is descriptive qualitative research with the research subjects being all students of class VI, totaling 24 students, guardians of class VI, and the principal of SD Muhammadiyah 9 Surabaya. Data collection techniques used were student questionnaire sheets, teacher interview sheets, and school principals. This study uses analytical techniques consisting of data collection, data reduction, data presentation, and conclusion drawing. Data based on the results of research conducted there are 93% of students stated that they enjoyed participating in limited face-to-face learning compared to online, 95% felt motivated, 95% said the learning atmosphere was more enjoyable, 90% said the material was easier to understand and 95% said study time was more effective. According to the homeroom teacher for grade VI, through the use of this science learning video, the teacher felt that the learning time could be used more effectively, even though there were several obstacles faced by the teacher. Likewise, according to the principal, the use of video media is in accordance with the character of the digital generation of students. Based on the results of the research above, it can be concluded that learning using science learning videos is very suitable for use in limited face-to-face learning.